The colonic flap: a versatile and reliable donor-site-free technique for pelvic reconstruction after exenteration - Sahakitrungruang, Chucheep; Malakorn, Songphol (Frontiers in Oncology, 2025)
Pelvic exenteration for locally advanced or recurrent malignancies results in a large pelvic dead space and complex perineal defects, presenting formidable reconstructive challenges. Conventional methods, such as the vertical rectus abdominis myocutaneous (VRAM) flap, are effective but associated with significant donor-site morbidity and flap-specific complications. To overcome these limitations, the colonic flap was developed, a technique that utilizes a vascularized segment of sigmoid colon harvested within the operative field. This approach has two main applications: a mucosa-intact sigmoid flap for neovaginal reconstruction, and a mucosa-removed colonic flap for pelvic floor reconstruction and dead-space obliteration. This review outlines the limitations of existing techniques, the rationale for the colonic flap, its surgical principles, indications, clinical outcomes, and limitations. Based on more than a decade of clinical experience, the colonic flap has proven to be a safe, versatile, and effective reconstructive option. It avoids donor-site morbidity, is fully compatible with minimally invasive surgery, and provides excellent functional and oncologic outcomes. The colonic flap should be considered a valuable addition to reconstructive options in advanced pelvic surgery.